Review of Floating Solar Photovoltaic Researches in Indonesia (Journal of Electrical, Electronics and Informatics, 2026)
The increase interest of emission reduction of electricity sector in Indonesia has driven the exploration of renewable sources including Floating Solar Photovoltaic (FPV). This article reviews the development of FPV researches in Indonesia through systematic literature review. The collected data were analyzed based on waterbody type, geographical location, system configuration, floating technology, cell technology, and simulation tools. The analysis shows that FPV research are predominantly assessing the potential of reservoirs, lakes, and seas spread across Indonesian archipelago. Among 34 provinces of Indonesia, the provinces of East Java, West Java, and Bali are being the most active provinces as location for FPV researches. On-grid systems are the most commonly explored options as it is supported by government policies and existing grid infrastructure. The review shows the increased interests on assessing the potential of FPV in the Indonesian renewable energy sphere considering 2/3 of the nation is covered by water.
Keywords: Power generation; renewable energy; floating PV; FPV